Increasing inputs of invasive N-fixing Acacia litter decrease litter decomposition and associated microbial activity in streams - Pereira, Ana (2022)
1. Nitrogen (N)-fixing Acacia species are often aggressive invaders outside their native range. When invading native riparian temperate forests, they can decrease tree species diversity, alter the quality of litter inputs to streams and increase water N concentration. Although the effects of riparian tree species diversity and nutrient enrichment on litter decomposition and associated microbial decomposers have been widely studied, their individual and combined effects remain poorly understood, especially in streams flowing through forests invaded by Acacia species. Here, we assessed the effects of litter diversity (species evenness) and water N concentration on the decomposition of native and Acacia litter, and the activity and community structure of associated microbial decomposers. 2. Litter of Castanea sativa (C) and Acacia melanoxylon (A) was enclosed in finemesh bags in a total of five litter evenness treatments (100%C, 75%C + 25%A, 50%C + 50%A, 25%C + 75%A and 100%A), and immersed in a stream flowing through a native forest (native stream) and a stream flowing through a forest invaded by Acacia species (invaded stream). 3. Litter decomposition rates and microbial decomposer activity differed among litter evenness treatments, generally decreasing as the proportion of A. melanoxylon increased. When considered individually, C. sativa litter decomposition and associated microbial activity did not differ among treatments. For A. melanoxylon, decomposition rates did not differ among treatments, whereas microbial activity was generally lower in treatments with higher or even proportions of C. sativa. 4. Litter diversity had (small) antagonistic effects on litter decomposition in streams. However, litter treatments affected by diversity (species evenness) effects differed between streams, suggesting that effects can be modulated by water N concentration. 5. Litter decomposition rates and microbial decomposer activity were higher in the invaded than in the native stream, probably as a consequence of the higher water N concentration in the former stream. However, the magnitude of the effects was small owing to the fact that water N concentration was still in the oligothrophic range in the invaded stream. 6. Overall, our results suggest that the increasing proportion of N-fixing Acacia species in invaded deciduous riparian forests will affect litter decomposition rates and microbial decomposer activity, and alter aquatic hyphomycete community structure, most probably as a result of decreases in the diversity and quality of litter inputs to streams, and increases in water N concentration. However, the magnitude of the effects resulting from decreases in litter input diversity and quality (due to increases in Acacia contribution) into invaded streams will probably be larger than those resulting from increases in water N concentration, thus overall litter decomposition will decrease. These impacts will possibly alter nutrient cycles in aquatic food webs that depend on riparian detritus, with implications for stream functioning.